2.Write the additive inverse of each of the following:

(i)\(\frac{2}8 \)

(ii)\(\frac{-5}9 \)

(iii)\(\frac{-6}{-5} \)

(iv)\(\frac{2}{-9} \)

(v)\(\frac{19}{-6} \)

(i)\(\frac{2}8 \)

(ii)\(\frac{-5}9 \)

(iii)\(\frac{-6}{-5} \)

(iv)\(\frac{2}{-9} \)

(v)\(\frac{19}{-6} \)

We have additive inverse of a as a=-a .So, we have:

(i) Additive inverse of \(\frac{2}8 = \frac{-2}8\)

(ii)Additive inverse of \(\frac{-5}9 = -(\frac{-5}9)= \frac{5}9\)

(iii) we have \(\frac{-6}{-5}= \frac{6}5 \)

∴ the additive inverse of \(\frac{6}5 =\frac{-6}5\)

(iv)We have \(\frac{2}{-9}=\frac{-2}9\)

∴ Additive inverse of \(\frac{-2}{9} = -(\frac{-2}9)= \frac{2}9\)

(v)We have \(\frac{19}{-6}=\frac{-19}6\)

∴ Additive inverse of \(\frac{-19}{6} = -(\frac{-19}6)= \frac{19}6\)